Expressões referenciais e avaliação em ofícios dos séculos XVIII e XIX - Silva, Josefa Mônica Almeida (2007)
This research focuses on official letters written between brazilian colonial and imperial periods. It aims at investigating referential expressions as possible evaluation founders in this particular text genre. The theoretical basis for this work uses both Historical Linguistics and Text Linguistics assumptions, particularly the studies about referenciation. It analyses the characterization of subjectivity, denounced by referential expressions, as opposed to the impersonal tone/nature of these official correspondences. For studying the distribution of communicative unites in a corpus constituted by 37 official letters of Paraiba´s public administration of XVIII and XIX centuries, Silveira´s (2002) model was applied. For analyses of referential expressions, we used Cavalcante´s (2003) chart. The results achieved point to confirmation of our initial hypothesis that predicted the presence of the evaluation of the official correspondence issuers. Analyzing the data, we find that the estrategies that most contributed to the establishment of the evaluation were the references introductions and the coreferential anaphora. It is expected, with the results of this research, to contributes to the studies focused on the written form of Brazilian Portuguese, starting from the relation between official letter, language and argumentation.